Energy Integrated Distillation Columns Sequence (EIDC) of 5-Component Alcohol Mixture via Driving Force and Thermal Pinch Analysis Approach. - Shahruddin, Munawar Zaman; Xinyi, Tan; Rahimi, Ahmad Nafais; Zubir, Afiq; Zahran, Muhammad Fakhrul Islam; Ibrahim, Kamarul Asri; Hamid, Mohd Kamaruddin Abd (International Journal of Engineering and Technology, 2018)
Distillation column is a well-known unit operation to perform the intended separation task in chemical and petrochemical industries. However, the common issue for distillation column is the large energy requirement especially for multicomponent processes. Therefore, the sequence determination could be a key to solve the problem. This paper provides a methodology to produce energy integrated distillation columns sequence via driving force sequence approach. Then, it is supported by the thermal pinch analysis for further the energy saving in the process.  The case study selected is distillation process of 5-component alcohol mixture. Based on the input data, two sequences for distillation columns namely direct sequence and driving force sequence were firstly simulated. Then, the resulting information such as target temperature, supply temperature and energy from condensers and reboilers have been extracted for thermal pinch analysis. Lastly, the energy requirements from the analysis (before and after pinch analysis) were compared for energy saving calculation. Based on the analysis results, the driving force sequence with pinch analysis successfully enhanced the 35% of the overall energy saving. Thus, it can be said that the driving force sequence and thermal pinch analysis approach namely energy integrated distillation columns sequence has a potential for further the energy saving of the distillation columns sequence for the selected case study.